Impact of blast exposure on visual pathway: Mechanism exploration and novel diagnostic perspectives - Yue Wang; Nan Yang; Xiaofan Chen; Xing Chen; Yalei Ning; Rongdi Yuan (PLoS ONE, 2026)
Blast-induced traumatic brain injury (bTBI), frequently observed in modern warfare, often presents without overt clinical symptoms initially, yet can involve visual impairment. However, the underlying mechanisms and long-term outcomes of visual dysfunction following blast exposure (BE) remain poorly understood. This study aimed to investigate the potential delayed effects of BE on visual function. A bTBI mouse model was established using a biological shock tube. Neurological deficits were assessed via the modified neurological severity score, while visual function was evaluated at multiple time points using flash visual evoked potentials (F-VEP) and a light-dark shuttle box. Ultrastructural evidence of damage was obtained through transmission electron microscopy (TEM). Inflammatory and pyroptosis markers were localized and quantified via immunofluorescence staining and Western blotting. Neuronal damage was detected by the terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining combined with neuron-specific nuclear protein (NeuN) immunofluorescence labeling. To assess therapeutic potential, MCC950 was administered to bTBI mice, and visual function was re-evaluated. The results demonstrated that visual dysfunction emerged at 24 hours post BE, followed by a transient recovery, and reappeared at 28 days post BE. Early demyelination of the optic nerve and later pyroptosis of neurons in the visual cortex were identified as key pathological features. MCC950 treatment effectively mitigated neuroinflammation and neuronal pyroptosis, thereby ameliorating late-phase visual dysfunction. These findings collectively suggest that BE leads to biphasic visual dysfunction, driven by distinct mechanisms at different stages. Early intervention targeting nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation may represent a promising therapeutic strategy to prevent late-phase visual impairment. Moreover, non-invasive F-VEP provides a sensitive and practical approach for assessing visual injury in bTBI.